2003
DOI: 10.1046/j.1464-5491.2003.01068.x
|View full text |Cite
|
Sign up to set email alerts
|

The Metabolic Syndrome is an independent predictor of cardiovascular disease in Type 2 diabetic subjects. Prospective data from the Verona Diabetes Complications Study

Abstract: In Type 2 diabetes, the presence of the Metabolic Syndrome is associated with an almost 5-fold increase in CVD risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
139
1
16

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(165 citation statements)
references
References 24 publications
9
139
1
16
Order By: Relevance
“…Our finding that metabolic syndrome predicted CVD death is in agreement with results from previous studies in non-diabetic [27][28][29] and type 2 diabetic subjects [30,31]. In the study of Bonora et al [30], no sex-related differences were found in the prediction of CVD among type 2 diabetic patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our finding that metabolic syndrome predicted CVD death is in agreement with results from previous studies in non-diabetic [27][28][29] and type 2 diabetic subjects [30,31]. In the study of Bonora et al [30], no sex-related differences were found in the prediction of CVD among type 2 diabetic patients.…”
Section: Discussionsupporting
confidence: 92%
“…In the study of Bonora et al [30], no sex-related differences were found in the prediction of CVD among type 2 diabetic patients. Our finding that among non-diabetic subjects metabolic syndrome was a stronger predictor of CVD mortality in women than in men is of interest.…”
Section: Discussionmentioning
confidence: 81%
“…It is well known that type 2 diabetes is accompanied by an increased risk of CVD independently of conventional cardiovascular risk factors such as hypertension or dyslipidemia [14,15]. Furthermore, the relative risk for CVD in type 2 diabetic patients with metabolic syndrome diagnosed by NCEP-ATP III definition is greater than in those without metabolic syndrome, and its risk is modified by the number of components of metabolic syndrome [16][17][18]. However, whether the new definition of metabolic syndrome in which central obesity is mandatory is a better predictor of CVD than the individual components of metabolic syndrome in type 2 diabetic patients has not yet been clarified.…”
mentioning
confidence: 99%
“…Type 2 diabetes represents a paradigmatic condition in which the metabolic syndrome is highly prevalent (27,28) and often precedes the onset of hyperglycemia. Furthermore, insulin resistance and the metabolic syndrome predict atherosclerosis in type 2 diabetic patients (12,27).…”
mentioning
confidence: 99%